Photocatalyst-, metal- and additive-free, direct C-H arylation of quinoxalin-2(1H)-ones with aryl acyl peroxides induced by visible light - Xu, Jun; Zhang, Hongdou; Zhao, Jianming; Ni, Zhigang; Zhang, Pengfei; Shi, Bing-Feng; Li, Wanmei (ORGANIC CHEMISTRY FRONTIERS, 2020)
A visible light-mediated direct C-H arylation of quinoxalin-2(1H)-ones with aryl acyl peroxides has been developed. The reaction proceeds smoothly through a radical process in the absence of photocatalyst, additive and metal catalyst, providing the corresponding products in moderate to good yields. This methodology opens a simple and green access to 3-arylquinoxalin-2(1H)-ones.